Словото Божјо и Светото Писмо. Богословието како пат кон охристовување на човекот - Stefan Gogovski (ПБФ „Свети Климент Охридски“ - Скопје, 2020)
This paper is an attempt to articulate both rational and spiritual dimensions of Orthodox Theology which in a consecutive manner allows the understanding of its foundation roots – the Holy Bible and the Holy Tradition, without which is impossible to understand God – The Creator of the natural world and all beings, as the purpose of creation. Therefore, the accent is set on analyzing the anthropological and interpersonal structure of the bonding betweeen God and man. The necessity of true understanding, the intrinsecal connection of Orthodox Theology with the Orthodox faith in The Holy Trinity, as well as its well known cristian tradition and ecclesiological culture are crucial element for understanding the doctrine on which alongside the Orthodox Theology and its academic growth are based. The most important aspect of Orthodox Christian theology is the teaching related to theosis or deification. In fact, it is another way of stating the doctrine of humanity’s creation in the image and likeness of God. While ‘image’ emphasizes the ontological beginning of humanity, theosis emphasizes the ontological end or thelos of man. Both state that ‘authentic humanity’ is recognized only in relationship with the divine prototype of humanness. That indicates that human perfection is intimately and fundamentally related to Divine perfection. When the doctrine of the image, particularly in its patristic form, ad the doctrine of theosis are related to this call for perfection, they form a coherent whole.
Словата и Словото – Зборник на научни трудови од Третиот Светиклиментов научен собир